2009
DOI: 10.1890/08-0238.1
|View full text |Cite
|
Sign up to set email alerts
|

Top‐down effects on antagonistic inducible defense and offense

Abstract: Abstract. Antagonistic phenotypic plasticity may strongly influence trait evolution in tightly interacting predator-prey pairs as well as the role that trait plasticity plays in community dynamics. Most work on trait plasticity has focused on single predator-prey pairs, but prey must often contend with multiple predators in natural environments. Hence, a better understanding of the evolutionary and ecological significance of phenotypic plasticity requires experiments that examine how multiple predators shape p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
64
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 82 publications
1
64
0
Order By: Relevance
“…In contrast, when reduced defenses are a product of reduced interactions between a prey and its predator, modification of the inducible response may not reduce prey fitness. Our recent study (Kishida et al 2009a) illustrates this point. We found that induced morphological defenses in Rana pirica tadpoles against predatory salamander larvae were reduced by the presence of other predator (i.e., dragonfly larvae).…”
Section: Modification By External Factorsmentioning
confidence: 62%
See 4 more Smart Citations
“…In contrast, when reduced defenses are a product of reduced interactions between a prey and its predator, modification of the inducible response may not reduce prey fitness. Our recent study (Kishida et al 2009a) illustrates this point. We found that induced morphological defenses in Rana pirica tadpoles against predatory salamander larvae were reduced by the presence of other predator (i.e., dragonfly larvae).…”
Section: Modification By External Factorsmentioning
confidence: 62%
“…Modification of trait plasticity by other community members has also been observed for inducible offensive morphologies in predators (Andersson et al 2007;Kishida et al 2009a). Kishida et al (2009a) examined how a top-predator affects antagonistic inducible offense and defense between salamanders and tadpoles, using a dragonfly -salamander -tadpole intraguild predation system.…”
Section: Modification By External Factorsmentioning
confidence: 78%
See 3 more Smart Citations